Computer Assisted Teaching Methodology - Safei, Su'aidi (2007)
The workshop focused on the incorporation of Information Communication Technology (ICT) in teaching methodology facilitated by Assoc.Prof.Dr.Hj.Su'aidi Dato'Hj.Safei. It is to expose the lecturers to the importance of changing and shifting teaching approach and strategy by using modern technology. If we don't update ourselves, we might become obsolete.